A rare case of primary rectal choriocarcinoma and review of the literature - ATICI, ALİ EMRE; DEMİRCAN, NAZIM CAN; ERGELEN, RABİA; YUMUK, PERRAN FULDEN; ARIKAN, RUKİYE (SAGE PUBLICATIONS LTD, 2020)
Introduction Primary choriocarcinoma of the colon is an extremely rare neoplasm which has a poor prognosis. Only 18 cases have been previously reported in English medical literature. Here we present a case of primary rectal choriocarcinoma with a good response to chemotherapy and review the literature on this uncommon tumor. Case report A 36-year-old woman presented with abdominal pain and vaginal bleeding. Abdominal magnetic resonance imaging revealed 6.9 x 5.3 x 6.4 cm hypervascular mass posterior to uterus very close to rectum. Beta-human chorionic gonadotropin (beta-hCG) level was markedly elevated. Low anterior resection of the rectum with lymph node dissection and total abdominal hysterectomy with bilateral salpingo-oophorectomy were performed. Pathologic diagnosis was reported as colonic choriocarcinoma with a focal component of adenocarcinoma. Post-operative magnetic resonance imaging detected multiple metastatic lesions throughout the liver. The patient was treated with systemic chemotherapy using bleomycin, etoposide and cisplatin (BEP protocol). After three cycles, beta-hCG level decreased to normal and magnetic resonance imaging showed regression of liver metastasis. However, the patient died of respiratory failure due to bleomycin toxicity and pneumonia accompanied by rapid disease progression. Discussion This is an extremely rare case of primary rectal choriocarcinoma. Due to poor prognosis of the disease, it seems very important to start prompt treatment to improve patient's survival.
Keywords: Choriocarcinoma; colorectal; chemotherapy; SIGMOID COLON; ADENOCARCINOMA; DIFFERENTIATION; COEXISTENCE; METAPLASIA